VULNERABLITY OF RURAL LIVELIHOODS IN NINH THUAN PROVINCE TO DROUGHT - Tan Luc Chau; Ha Anh Hoang; Thai Hiep Vo; Thanh Ha Dang (Tạp chí Khoa học Đại học Đà Lạt)
The risk of drought poses a significant challenge to agricultural production in Ninh Thuan Province. Therefore, this study aims to identify the factors that influence farmers’ livelihood outcomes due to the impact of drought. Data were collected from a survey of 231 farmers randomly selected from the districts of Thuan Nam, Thuan Bac, and Ninh Hai. In addition to descriptive statistics, a Tobit regression model was used to identify the factors influencing livelihood outcomes during mild and severe droughts. The results showed that farmers’ livelihood outcomes were generally low. The regression identified the financial (β=0.230 and 0.205), social (β=0.200 and 0.291), and human capital (β=0.195 and 0.196) impacts on farmers’ livelihood outcomes from both mild and severe droughts. During mild drought years, seasonal adjustment (β=-0.009) and migration (β=0.013) were found to significantly influence livelihood outcomes. In severe drought years, government support (β=-0.030) negatively affected livelihood outcomes. There is a need to establish an early warning system for climate change and extreme weather events while simultaneously disseminating information widely to farmers so that they can take timely measures to cope. Enhancing human capital by raising awareness and skills in adapting to drought and developing comprehensive abilities to implement drought adaptation strategies is needed.